Regulasi Diri dalam Belajar pada Mahasiswa yang Memiliki Peran Banyak - Dwi Nur Rachmah (Jurnal Psikologi, 2015)
This study aimed at identifying and understanding more deeply the self-regulated learning of students with a high GPA, who had multiple roles (as housewives and workers also). The approach employed in this study was the qualitative-phenomenological approach. The subjects of the study were selected by purposive sampling technique and the data were collected using techniques of observations and in-depth interviews. The results indicated that the four subjects conducted self-regulation in learning through regulating cognition, motivation, behavior, and emotion. Moreover, the subjects performed context regulation in order to achieve certain learning objectives. Self-regulated learning performed by the subjects was influenced by specific precipitating situations and the characteristics of each related individual. It was also strengthened by social support given to them.